A diagnostic dilemma in an alert patient with pulmonary oedema following craniotomy: A case report☆. (December 2017) - Tsubaki, Kosuke; Inoue, Satoki; Kawaguchi, Masahiko
ABSTRACT : Introduction: : We present a case developing idiopathic pulmonary oedema following craniotomy without any neurological symptoms. Case description: : A 70‐year‐old female, who had unremarkable medical history, underwent removal of brain tumour under general anaesthesia. Craniotomy was uneventfully performed and her respiratory and haemodynamic conditions during the operation were normal. Immediately after the operation, she regained consciousness and was neurologically intact. However, her oxygenation was not sufficient without oxygen administration, her chest X‐ray showed pulmonary oedema. Gradually, her pulmonary oedema in the chest Xrays disappeared. There was no specific reason of pulmonary oedema except for intracranial manipulation, therefore, it was considered as neurologic pulmonary oedema. Conclusion: : In this case, we merely might have followed the restoration process from neurologic pulmonary oedema developing during the operation. Dilema diagnóstico en un paciente despierto con edema pulmonar tras craneotomía: reporte de caso: RESUMEN: Introducción: : Presentamos un caso de desarrollo de edema pulmonar idiopático tras craneotomía sin síntomas neurológicos. Descripción del caso: : Una paciente de sexo femenino de 70 años de edad con una historia médica sin interés se sometió a una extirpación de tumor cerebral bajo anestesia general. La craneotomía se realizó sin eventos notables y sus condiciones respiratorias y hemodinámicas durante la operación se mantuvieron normales. Inmediatamente al concluir la operación la paciente recobró su conciencia y se encontró en estado neurológico intacto. Sin embargo, su oxigenación no era suficiente sin administración de oxígeno, y las radiografías indicaban edema pulmonar. Gradualmente su edema pulmonar visualizado en las radiografías torácicas desapareció. No había ninguna razón para el edema pulmonar excepto manipulación intracraneal, así que fue considerado como un edema pulmonar neurológico. Conclusión: : En este caso, habríamos simplemente seguido el proceso de restauración del edema pulmonar neurológico que se desarrolló durante la operación.